LGBT Representation In You Need To Calm Down-Taylor Swift Music Video - Fadeliyah Ikhwan; Muh. Akbar; Muliadi Mau (Universitas Lambung Mangkurat, 2025)
Music videos have become a popular medium for conveying social messages. This study analyzes the representation of Lesbian, Gay, Bisexual, and Transgender (LGBT) messages in Taylor Swift's music video